Analiz rezul'tatov mužskoj sbornoj komandy Rossii na 49-m cempionate mira po sportivnoj gimnastike 2019 goda v Štutgarte (Germanija) - Somkin, A. A. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article provides the analysis of the Russian National men`s team results at the qualification competitions, team final, individual all-around and apparatus finals at the 49th FIG Artistic Gymnastics World Championships 2019 in Stuttgart (Germany). At these championships the Russian team became the champion in team competitions - for the first time in history. The special attention in the publication is paid to the best results of the all-around World champion Nikita Nagornyy and silver prize winner Artur Dalaloyan at these world championships and for the upcoming 2020 Olympic Games in Tokyo (Japan).